Race Representation and the Concept of Religiosity in Genshin Impact - Putri, Lintang Shabrina; Aji, Angga Prawadika (Jurnal Media dan Komunikasi Indonesia, 2025)
The video game trend in Indonesia has witnessed an escalation since 2020, with one of the popular games among the populace being Genshin Impact. Genshin Impact is a role-playing gaming (RPG) video game, that immerses players in a narrative-driven experience where they embody avatars to navigate the game's missions. In the context of RPG, the meticulous construction of the game world is pivotal to bolstering the overarching storyline. Consequently, the significance of representation cannot be overstated, serving as a linchpin for enhancing the gaming experience. This contextual backdrop frames the present research, seeking to unravel the cultural portrayals embedded within Genshin Impact. The aspiration is to contribute novel insights to the discourse on representation studies. Moreover, the research employs a qualitative descriptive methodology, leveraging Roland Barthes' semiotic analysis to scrutinize the intricate cultural elements within the game. This analytical approach aims to uncover and comprehend the nuanced layers of cultural representation in Genshin Impact.